Storage Management System of Delivery Vehicle for PT Pos Indonesia (Persero) - Catherine Marcella; Agus Windharto (Jurnal Sains dan Seni ITS, 2019)
At present, 70% of shipments which served by logistics services are e-commerce goods weighing 0-4 kg. The speed of delivery and package security become important factors for both couriers and consumers. It is undeniable that vehicles become the key to successful delivery activities. But the challenge so far, the shipments is too large to be sent by a motorbike, but also too small to be sent by car and feared will be damaged or tucked away. The only solution is by implementing a storage management system so that the courier can load, arrange and unload the package from the vehicle easily. This article proposes a design of implementable storage management system for delivery vehicles so that delivery activities done by couriers become more effective and efficient. By analyzing storage requirements, the ideal cargo criteria will be known. After that, storage accessibility study will be conducted to find out more about storage operations on vehicle and its critical dimensions that will become the storage specifications. Through applying gravity principle, a simple shelving system is expected to be a solution for storage management of delivery vehicle.